3(0.9-1)-(x+0.6)=-0.2

Simple and best practice solution for 3(0.9-1)-(x+0.6)=-0.2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(0.9-1)-(x+0.6)=-0.2 equation:


Simplifying
3(0.9 + -1) + -1(x + 0.6) = -0.2

Combine like terms: 0.9 + -1 = -0.1
3(-0.1) + -1(x + 0.6) = -0.2

Multiply 3 * -0.1
-0.3 + -1(x + 0.6) = -0.2

Reorder the terms:
-0.3 + -1(0.6 + x) = -0.2
-0.3 + (0.6 * -1 + x * -1) = -0.2
-0.3 + (-0.6 + -1x) = -0.2

Combine like terms: -0.3 + -0.6 = -0.9
-0.9 + -1x = -0.2

Solving
-0.9 + -1x = -0.2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.9' to each side of the equation.
-0.9 + 0.9 + -1x = -0.2 + 0.9

Combine like terms: -0.9 + 0.9 = 0.0
0.0 + -1x = -0.2 + 0.9
-1x = -0.2 + 0.9

Combine like terms: -0.2 + 0.9 = 0.7
-1x = 0.7

Divide each side by '-1'.
x = -0.7

Simplifying
x = -0.7

See similar equations:

| x-5=20*10 | | 1/2x+3=1/3x+2 | | m=(2-1) | | w=4+15 | | 2(x-2)=2x-6 | | 2x-8x+4=x-9+13 | | 3x-14=3x-14 | | 1.1x+8=0.5x+20 | | 1.1x+8=0.5x+29 | | (20-2x)x=90 | | 5227.50=5100(1+.025r) | | y=9.5+100 | | y=-0.62+0.0005x | | y=-0.62+0.0005211x | | y=0.0005211x+-0.62 | | 2c+4+3c=-16 | | 2x^2+1=2x+12 | | 4y-5x=40 | | .6x+1.9x=5 | | .6x+1.9=5 | | 2x^2+43x-2730=0 | | a+5=3 | | 7-6(3-8x)=0 | | x^2-14x+36= | | log(100)=10 | | ?10x+1+7x=37 | | ?10x+1+7x=32 | | ?10x+1+7x= | | ?10x+1+7x=37 | | log(x+5)-log(1-5x)=0 | | .50(x-6)+1=2(x-10)-3 | | 6x+4+8x+18+(180-20x+4)=180 |

Equations solver categories